2019
DOI: 10.1088/1674-4527/19/7/93
|View full text |Cite
|
Sign up to set email alerts
|

Coherent structures and spectral shapes of kinetic Alfvén wave turbulence in solar wind at 1 AU

Abstract: This paper presents the generation of kinetic Alfvén wave (KAW) coherent structures of magnetic filaments applicable to solar wind at 1AU, when the background plasma density is modified by parallel ponderomotive force and Joule heating. The inhomogeneity in the magnetic field, which was included as a perturbation in the transverse direction of the magnetic field, takes energy from the main pump KAWs and generates the filamentary structures.When the intensity is high enough, the filaments are broken down and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…A fundamental and long standing problem in astrophysics is why the tenuous solar (and many stellar) corona has a million-degree temperature far in excess of the underlying vastly denser photosphere. More and more evidence has revealed that the heating energy is generated directly from the photosphere via hot expulsions, spicules or Alfvén waves (McIntosh et al 2011;Tian et al 2014;Peter et al 2014;Dinesh Singh & Singh Jatav 2019), but leaving no residual traces on it. Resolution of this problem ultimately relies on resolving fine-scale mass and energy flows passing through the chromosphere, the interface layer sandwiched between the photosphere and the transition region or the corona (De Pontieu et al 2014;Tian 2017;De Pontieu et al 2009;Aschwanden et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental and long standing problem in astrophysics is why the tenuous solar (and many stellar) corona has a million-degree temperature far in excess of the underlying vastly denser photosphere. More and more evidence has revealed that the heating energy is generated directly from the photosphere via hot expulsions, spicules or Alfvén waves (McIntosh et al 2011;Tian et al 2014;Peter et al 2014;Dinesh Singh & Singh Jatav 2019), but leaving no residual traces on it. Resolution of this problem ultimately relies on resolving fine-scale mass and energy flows passing through the chromosphere, the interface layer sandwiched between the photosphere and the transition region or the corona (De Pontieu et al 2014;Tian 2017;De Pontieu et al 2009;Aschwanden et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is very complicated to solve dynamical wave Eq. ( 38) analytically, hence the solution have carried out by numerical method [61,62].…”
Section: Numerical Simulation Resultsmentioning
confidence: 99%
“…This equation is also known as the modified NLS equation with the cubic-quintic (CQ) nonlinearity, see, e.g., [37,38] in the context of waves in optical media. In general, Equation ( 23) is valid for a wide range of physics [39][40][41][42]. Both nonlinear terms in it have the same order of magnitude, and, according to (17), (18) the signs of the nonlinear coefficients α 1 , α 3 in CQ NLS (23) are determined by the values and signs of the nonlinearity coefficients α 2 , α 4 and dispersion parameter β (always positive in the context of gravity waves in fluids) in the original Equation (1), that is, any combination of signs of nonlinearity coefficients ( α 1 , α 3 ) can occur in CQ NLS (23), and dispersion coefficient β 1 in (23) always has the opposite sign to the sign of β in Equation (1).…”
Section: Rescalingmentioning
confidence: 99%